Covering the environment : how journalists work the green beat - Wyss, Bob (ROUTLEDGE, 2019)
"This practical primer explains the primary issues in writing about the environment, identifies who to go to and where to find sources, and offers examples of writing and reporting the beat. Observations and story excerpts from experienced journalists provide real world context both for those in the U.S. as well as internationally. Practice story assignments, resources, and a glossary of critical terms gives budding journalists all the tools needed to cover the green beat. Updated with detailed coverage of how companies and climate change have evolved over the past decade, this second edition expands upon the digital sphere and the myriad ways that deadline, multimedia and mobile reporting have changed environmental journalism. Including consideration of issues such as the water crisis in Flint, Michigan, and the GMO controversy, this new edition provides a fresh take on the green beat with a newly organized table of contents and a guide to freelance and entrepreneurial journalism anyway in the world"--